Comparative and evolutionary genomics of secondarily temperate adaptation in a non-Antarctic icefish - Rivera-Colon, Angel G. (2023)
White-blooded Antarctic icefishes are a group of highly derived vertebrates, specialized to both the chronic cold of the Southern Ocean and life without hemoglobin. Their specialized phenotypes constrain icefishes mostly to the cold, highly oxygenated Antarctic waters. Yet, despite their extreme physiology, a single icefish species, the pike icefish Champsocephalus esox, successfully colonized and likely adapted to the temperate environments off the Patagonian coast of South America. However, the genetic mechanisms that enabled this polar-to-temperate transition from highly specialized Antarctic populations were previously unknown. In this work, I describe the first genomic characterization of a secondarily temperate icefish species, comparing both the genome and population-level variation of the temperate icefish (C. esox) against its Antarctic sister species (Champsocephalus gunnari). In the first research chapter (chapter 2), I describe the RADINITIO software, a pipeline for the simulation of RADseq experiments. Using this software, I model library construction parameters and identify sources of error that can impact RADseq experiments, which I then used to optimize empirical RADseq libraries used for genotyping C. esox and C. gunnari samples. In my second research chapter, I use the data from these RADseq libraries, in addition to generating chromosome-level genome assemblies for each species, to characterize the genomic architecture of secondarily temperate variation in C. esox. I find large-scale conservation in the structure and organization of temperate and Antarctic icefish genomes. However, I find evidence of structural variation in the C. esox lineage that co-localizes with regions of elevated genetic diversity and signatures of selection, highlighting possible candidate genes underlying temperate adaptation in this system. For my last research chapter, I expand on this RADseq analysis by implementing a novel Tree Sequence-based approach, which I use to reconstruct the genealogical relationships ...